Prevalence and Genetic Characteristics of Staphylococcus aureus CC398 Isolates From Invasive Infections in Spanish Hospitals, Focusing on the Livestock-Independent CC398-MSSA Clade - Mama, Olouwafemi Mistourath; Aspiroz, Carmen; Ruiz-Ripa, Laura; Ceballos, Sara; Iñiguez-Barrio, Maria; Cercenado, Emilia; Azcona, José Manuel; López-Cerero, Lorena; Seral, Cristina; López-Calleja, Ana Isabel; Belles-Belles, Alba; Berdonces, Pilar; et al. (Frontiers in Microbiology, 2021)
Background: Livestock-associated (LA)-CC398-MRSA is closely related to pigs being unfrequently detected in human invasive infections. CC398-MSSA is emerging in human invasive infections in some countries, but genetic and epidemiological characteristics are still scarcely reported. Objectives: To determine the prevalence of Staphylococcus aureus (SA) CC398, both MRSA and MSSA, among blood cultures SA isolates recovered in Spanish hospitals located in regions with different pig-farming densities (PD) and characterize the recovered isolates. Methods: 1022 SA isolates (761 MSSA, 261 MRSA) recovered from blood cultures during 6-12 months in 17 Spanish hospitals (2018-2019) were studied. CC398 lineage identification, detection of spa-types, and antibiotic resistance, virulence and human immune evasion cluster (IEC) genes were analyzed by PCR/sequencing. Results: Forty-four CC398-MSSA isolates (4.3% of SA; 5.8% of MSSA) and 10 CC398-MRSA isolates (1% of SA; 3.8% of MRSA) were detected. Eleven spa-types were found among the CC398-MSSA isolates with t571 and t1451 the most frequent spa-types detected (75%). Most of CC398-MSSA isolates were Immune-Evasion-Cluster (IEC)-positive (88.6%), tetracycline-susceptible (95.5%) and erythromycin/clindamycininducible-resistant/erm(T)-positive (75%). No statistical significance was detected when the CC398-MSSA/MSSA rate was correlated to PD (pigs/km2) (p=0.108). On the contrary, CC398-MRSA isolates were all IEC-negative, predominately spa-t011 (70%), and the CC398-MRSA/MRSA rate was significantly associated to PD (p < 0.005). Conclusions: CC398-MSSA is an emerging clade in invasive infections in Spanish hospitals. CC398-MRSA (mostly t011) and CC398-MSSA (mostly t571 and t1451) show important differences, possibly suggesting divergent steps in host-adaptation evolutionary processes. While CC398-MRSA is livestock-associated (lacking IEC-system), CC398-MSSA seems to be mostly livestock-independent, carrying human-adaptation markers.